Treatment abandonment in children with cancer: Does a sex difference exist? A systematic review and meta‐analysis of evidence from low‐ and middle‐income countries. Issue 4 (22nd September 2020) - Palagyi, Anna; Balane, Christine; Shanthosh, Janani; Jun, Min; Bhoo‐Pathy, Nirmala; Gadsden, Thomas; Canfell, Karen; Jan, Stephen
Abstract: In this systematic review and meta‐analyses, we sought to determine sex‐disparities in treatment abandonment in children with cancer in low‐ and middle‐income countries (LMICs) and identify the characteristics of children and their families most disadvantaged by such abandonment. Sex‐disaggregated data on treatment abandonment were collated from the available literature and a random‐effects meta‐analysis was conducted to compare the rates in girls with those in boys. Subgroup analyses were conducted in which studies were stratified by design, cancer type and the Gender Inequality Index of the country of study. Eighteen studies were included in the systematic review and of these studies, 16 qualified for the meta‐analysis, representing 10 754 children. The pooled rate of treatment abandonment overall was 30%. We observed no difference in the proportion of treatment abandonment in girls relative to estimates observed in boys (rate ratio [RR] 0.95, 95% CI: 0.79‐1.15; P = .61). There was significant heterogeneity across the included studies and in the pooled estimate of RR for girls vs boys (both I 2 > 98%). Subgroup analyses did not reveal any effect on abandonment risk. Risk factors for abandonment observed fell into three main categories: socio‐demographic; geographic; and travel‐related. In conclusion, a high rate of treatment abandonment (30%) was observed overall for children with cancer in included studies in LMICs, although this was variable and context specific. No evidence of gender bias in childhood cancer treatment abandonment rates across LMICs was found. Given that the risk factors for abandonment are context specific, in‐depth country‐level analyses may provide further insights into the role of a child's gender in treatment abandonment decisions. Abstract : What's new? Treatment abandonment is a major cause of treatment failure in children with cancer in resource poor settings. Multiple factors potentially influence rates of treatment abandonment in childhood cancers, although very few studies have examined the influence of a child's gender. Here, analyses of treatment abandonment rates among boys and girls with cancer in low‐ and middle‐income countries uncovered no evidence to support gender bias. Treatment abandonment, however, was significantly linked to sociodemographic factors, including socioeconomic status and rural residence, indicating that risk factors for abandonment are context specific. Future in‐depth studies are needed to better understand treatment abandonment decisions.